Phase III randomized study of second line ADI-PEG 20 plus best supportive care versus placebo plus best supportive care in patients with advanced hepatocellular carcinoma. (5th April 2018) - Abou-Alfa, G K; Qin, S; Ryoo, B -Y; Lu, S -N; Yen, C -J; Feng, Y -H; Lim, H Y; Izzo, F; Colombo, M; Sarker, D; Bolondi, L; Vaccaro, G; et al.
Abstract: Background: Arginine depletion is a putative target in hepatocellular carcinoma (HCC). HCC often lacks argininosuccinate synthetase, a citrulline to arginine-repleting enzyme. ADI-PEG 20 is a cloned arginine degrading enzyme—arginine deiminase—conjugated with polyethylene glycol. The goal of this study was to evaluate this agent as a potential novel therapeutic for HCC after first line systemic therapy. Methods and patients: Patients with histologically proven advanced HCC and Child-Pugh up to B7 with prior systemic therapy, were randomized 2 : 1 to ADI-PEG 20 18 mg/m 2 versus placebo intramuscular injection weekly. The primary end point was overall survival (OS), with 93% power to detect a 4–5.6 months increase in median OS (one-sided α = 0.025). Secondary end points included progression-free survival, safety, and arginine correlatives. Results: A total of 635 patients were enrolled: median age 61, 82% male, 60% Asian, 52% hepatitis B, 26% hepatitis C, 76% stage IV, 91% Child-Pugh A, 70% progressed on sorafenib and 16% were intolerant. Median OS was 7.8 months for ADI-PEG 20 versus 7.4 for placebo ( P = 0.88, HR = 1.02) and median progression-free survival 2.6 months versus 2.6 ( P = 0.07, HR = 1.17). Grade 3 fatigue and decreased appetite occurred in <5% of patients. Two patients on ADI-PEG 20 had ≥grade 3 anaphylactic reaction. Death rate within 30 days of end of treatment was 15.2% on ADI-PEG 20 versus 10.4% on placebo, none related to therapy. Post hoc analyses of arginine assessment at 4, 8, 12 and 16 weeks, demonstrated a trend of improved OS for those with more prolonged arginine depletion. Conclusion: ADI-PEG 20 monotherapy did not demonstrate an OS benefit in second line setting for HCC. It was well tolerated. Strategies to enhance prolonged arginine depletion and synergize the effect of ADI-PEG 20 are underway. Clinical Trial number: www.clinicaltrials.gov (NCT 01287585).